2014
DOI: 10.1097/ijg.0b013e318264cd68
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Surface Disease Exacerbated Glaucoma

Abstract: Patients with severe OSD often have glaucoma that is refractive to medical therapy. Furthermore, the surgical success of glaucoma filtering surgery is compromised in patients with scarring and inflammation of the conjunctiva. The term we postulate is "OSD exacerbated glaucoma." This is the first study to suggest that the use of a combination approach comprising medical treatment to manage the OSD in patients with primary open angle glaucoma may lead to an improvement in the IOP control and the management of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 15 publications
(13 reference statements)
1
24
0
2
Order By: Relevance
“…It has been established, however, that combined antiglaucoma therapy can adversely influence adherence, tolerability, and ocular tissue health [46]. These parameters markedly reduce the success of long-term medical therapy [6, 7]. Treatment advances have been introduced to facilitate the success of combined therapy in real life.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established, however, that combined antiglaucoma therapy can adversely influence adherence, tolerability, and ocular tissue health [46]. These parameters markedly reduce the success of long-term medical therapy [6, 7]. Treatment advances have been introduced to facilitate the success of combined therapy in real life.…”
Section: Introductionmentioning
confidence: 99%
“…There was a trend towards lowering IOP following OSD treatment; furthermore, 58% of the eyes had an IOP reduction of at least 2 mmHg after OSD treatment. These findings can be explained either by the minimization of inflammatory stimuli that could affect the trabecular meshwork, 22,29 or by a significant increase in compliance due to the reduced discomfort. Although only one patient reported having missed more than one antiglaucoma drop in a week through our questionnaire, self-reported compliance is questionable and often overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…21 OSD management in glaucoma patients has been previously investigated, demonstrating clinical and symptomatic improvement along with better IOP control in a sample of four patients evaluated by subjective parameters. 22 This study aims to evaluate the prevalence of OSD in glaucoma patients under topical treatment, quantifying symptoms and measuring objective ocular surface parameters. Furthermore, this study evaluates the impact of OSD treatment on IOP control, improvement of ocular surface parameters and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, ocular hypertension resolved in 67% of the patients after lowering the dose of topical or systemic corticosteroids. Interestingly, one report showed that improvement in the ocular surface condition enhanced IOP control in patients with glaucoma and concurrent ocular surface disease [15]. The decision to treat ocular hypertension with anti-glaucoma medications should weigh the risks of sustained OHT against their toxicity on the ocular surface.…”
Section: Discussionmentioning
confidence: 99%
“…The use of steroids, the presence of inflammation, and scarring are some of the suggested mechanisms that lead to increased intraocular pressure (IOP) in patients with ocular surface disease [10,12,14,15]. Systemic corticosteroids are a standard treatment in many patients with systemic GVHD, and patients with ocular GVHD usually receive topical corticosteroids.…”
Section: Introductionmentioning
confidence: 99%